2015
DOI: 10.1007/s13224-015-0730-9
|View full text |Cite
|
Sign up to set email alerts
|

Value of MRI in Characterizing Adnexal Masses

Abstract: Magnetic resonance imaging (MRI) increases the specificity of imaging evaluation for adnexal masses, especially when they are indeterminate on ultrasound, very large or when further imaging is required to establish tissue characteristics. This article is a pictorial essay describing the value of MRI in characterizing adnexal masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Several imaging modalities are available for making a specific diagnosis among patients with adnexal mass ( 50 ). However, these modalities cannot replace histopathology or biopsy as the gold standard for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several imaging modalities are available for making a specific diagnosis among patients with adnexal mass ( 50 ). However, these modalities cannot replace histopathology or biopsy as the gold standard for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging plays an important role in the early diagnosis of ovarian cancers, thus improving the surgical results and decreasing morbidity and mortality rates (13). The MRI is a leader in increasing the characterization of adnexal masses and thus increasing the specificity particularly for indeterminate lesions by ultrasound and for extremely large masses (14). The present study revealed validity results of MRI in the diagnosis of malignant adnexal tumors as sensitivity (90.9%), specificity (75%), +ve predictive value (90.9%), -ve predictive value (75%) and accuracy (86.6%).…”
Section: Discussionmentioning
confidence: 99%
“…2 Levels below 35 U/mL were considered normal. 3 Large (more than 12/12 cm) solid, fixed or irregular adnexal masses suspicious of malignancy were treated by laparotomy. Trans-vaginal ultrasound scanning was used as primary imaging (Matsushita H et al).…”
Section: Methodsmentioning
confidence: 99%
“…The predictive value is about 96% in detection of the benign masses. 3 The procedure, being non-invasive, is widely acceptable for establishing the diagnosis. Magnetic resonance imaging (MRI) increases the specificity of imaging evaluation for adnexal masses, especially when they are indeterminate on ultrasound.…”
mentioning
confidence: 99%